Design Concept of Dairy Milk Edu-Tourism in Pakem District Using a Tropical Architecture Approach - Dhorika Husniawan; Rachmat Wahyu Prabowo (ARCHIHUMANUM, 2026)
Indonesia's dairy milk production remains low, requiring imports to meet more than 80% of national demand. Sleman, particularly Pakem District, has significant potential as a dairy cattle center, but limitations in business scale, technology, and sanitation prevent optimal productivity. Meanwhile, tourism in the Special Region of Yogyakarta (DIY) continues to grow, opening up opportunities for integrating livestock farming with ecotourism as a strategy for economic diversification and public education. This study aims to design a dairy ecotourism area in Pakem using a tropical architectural approach that is adaptive to the local climate, sustainable, and supports educational and recreational functions. The methods used include data collection, site analysis, space requirements, and precedent studies. The resulting design emphasizes open mass composition, flexible circulation, shaded facades, productive landscapes, and environmentally friendly utility systems. This design is expected to become a model for ecotourism that increases the economic value of livestock farmers, strengthens public awareness of healthy food, and emphasizes the relevance of tropical architecture in the Merapi slopes.